2023
DOI: 10.1177/17588359231179309
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of outcome following PSMA-based radioligand therapy and mechanisms of resistance in patients with metastatic castration-resistant prostate cancer

Abstract: [177Lu]Lu-PSMA has recently been approved for use in the post-taxane, post-novel hormonal-agent setting in patients with metastatic castration-resistant prostate cancer. As a beta-emitting radioligand targeting prostate-specific membrane antigen (PSMA), it delivers radiation to cells expressing PSMA on their surface. In pivotal clinical trials, patients were selected for this treatment based on positron emission tomography (PET)/CT imaging, requiring PSMA-avid disease with no evidence of discordant disease on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…The response rate in our patient group remained high and 84% of patients responded to subsequent cycles of 177 Lu-PSMA-RLT after the first treatment-free interval and following progression. Previously described resistance mechanisms do not seem to be associated with an increased number of treatment breaks or distribution of treatment cycles over longer periods [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The response rate in our patient group remained high and 84% of patients responded to subsequent cycles of 177 Lu-PSMA-RLT after the first treatment-free interval and following progression. Previously described resistance mechanisms do not seem to be associated with an increased number of treatment breaks or distribution of treatment cycles over longer periods [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that higher pretreatment PSMA-PET uptake is associated with improved overall survival thereby establishing a cut-off of SUVmean >10 for optimized patient selection (34). Yet, despite optimal standard PET/CT imaging, some patients demonstrate primary disease progression (35). Moreover, some of the patients with non-optimal standard PET/ CT imaging might still benefit from treatment (36).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, precise tumor burden quantification might be a valuable tool for assessing an individual's risk and prospective prognosis. Studies have shown that parameters such as metabolic tumor volume (MTV), an imaging-derived metric, serve as predictors for outcomes in various types of cancer treated with RNT [34][35][36]. While manual evaluations of tumor burden offer crucial insights, they are labor-intensive, which hampers the routine use of volumetric parameters like MTV in clinical practice.…”
Section: Patient Selection and Risk Stratificationmentioning
confidence: 99%